Normalizing calf circumference to identify low skeletal muscle mass in older women: a cross-sectional study - Gareth Stratton (Nutrición Hospitalaria, 2021)
Introduction: functional limitation is a result of sarcopenia and is associated with loss of skeletal muscle mass (SMM). Cost-effective methods are important for the identification of sarcopenia. Objective: to propose cutoff points for normalized calf circumference (CC) in order to identify low SMM in older women based on their functional limitation. Methods: in this descriptive, cross-sectional study the CC values of a young female sample (n = 78) were used to establish cutoff points (-2 SD) for low SMM in older women (n = 67). Functional limitation was identified by the six-minute walk test (≤ 400 m). CC was normalized by body mass, height, and BMI. The diagnostic accuracy of CC was calculated with a ROC curve, using functional limitation as standard. Results: cutoff points and area under the curve (AUC) were: CC (≤ 28.5; 0.62); CC·body mass-1 (≤ 0.40; 0.63); CC·height-2 (≤ 8.52; 0.55) and CC·BMI-1 (≤ 1.10; 0.73). Only CC·BMI-1 achieved a desirable accuracy (AUC > 0.7) to distinguish functional limitation. Conclusion: the accuracy attained supports the use of CC·BMI-1 to identify low SMM in older women. In the clinical context it is possible to predict the risk of sarcopenia when sophisticated methods for determining SMM are not available.